Abuse of Power on Managing the Health Care Services Policy for the Indonesian National Army Forces and its Implication on Marginalized Soldier’s Health - Purwalaksana, Ida Bagus; Sumartono; Haryono, Bambang Santoso; Wike; Riyadi, Bambang Slamet (International Journal of Criminology and Sociology, 2021)
This research aims to understand the abuse of power on managing the health service policy and its implication that is very significant in reducing marginalized soldiers’ health due at the ontological level and sociological level. The problem is very interesting to be analyzed by conducting a qualitative research method based on public policy theory, abuse of power theory, and health services theory. Data were collected through in-depth interviews, observation, and documentation related to managing the health service policy cases in Indonesia. Data were analyzed by using interactive models are data reduction, data display, data verification, and supported by triangulation. The results were based on ontological level and sociological level using public policy perspective and power perspective for improving health service policy and practice for The Indonesian Army Forces. Vision and mission of public policy on managing health service policy are needed for providing information to stakeholders related, regarding the regulations and sanctions in health service policy. This result provides inputs for making better regulation on health service policy in Indonesia for state agencies as public officials and practitioners.